1991
DOI: 10.1007/bf01986356
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove forest structure and productivity in the Fly River estuary, Papua New Guinea

Abstract: Abstract. In April, July and August 1989 and February 1990, the delta region of the Fly River was surveyed to establish the aerial extent of mangrove forests, their species composition, tree densities and basal areas, and potential net primary production. Mangrove forests cover 87 400 ha, mainly on islands within the delta. Twentynine mangrove plant species were recorded, but there were only three major forest types in the delta. Rhizophora apiculata-Bruguiera parviflora forests (hereafter Rhizophora-Bruguier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 21 publications
2
28
0
2
Order By: Relevance
“…The perception of productivity in mangrove forests is similar to Robertson et al, (1991) report to productivity increasing variance form rate of natural resource. However, in the dimension of villagers' concentration with primary productivity only, it does not cover to biomass carbon absorption issue (Amarasinghe & Balasubramaniam, 1992).…”
Section: Productivity In Mangrove Forestsupporting
confidence: 80%
“…The perception of productivity in mangrove forests is similar to Robertson et al, (1991) report to productivity increasing variance form rate of natural resource. However, in the dimension of villagers' concentration with primary productivity only, it does not cover to biomass carbon absorption issue (Amarasinghe & Balasubramaniam, 1992).…”
Section: Productivity In Mangrove Forestsupporting
confidence: 80%
“…Some studies found the similar distribution of Nypa, such as Bunt et al (1982); Hamilton and Murphy (1988); Robertson et al (1991), Ukpong et al (1991) and Theerawitaya et al (2014). Ukpong et al (1991) represented that Nypa distribution had a significant and negative correlation to salinity.…”
Section: Discussionmentioning
confidence: 89%
“…Ukpong et al (1991) represented that Nypa distribution had a significant and negative correlation to salinity. Robertson et al (1991) found that N. fruticans was growth in 1-10 ppt salinity range.…”
Section: Discussionmentioning
confidence: 95%
“…The mangroves of the Gulf of Papua are considered to be important nursery areas for fish and prawns (Birkeland 1985;Robertson and Duke 1987;Robertson et al 1991Robertson et al , 1998. They support a characteristic fish fauna in addition to forming a marginal habitat for both marine and riverine species.…”
Section: Mangroves In the Gulf Of Papua New Guineamentioning
confidence: 99%